Penerapan metode eksperimen mencampur warna dengan media cat air di TK Aisyiyah Pekalongan - Anna Diana Shanty (Action Research Journal, 2021)
Activities that involve students directly are very meaningful, especially activities that can develop children's talents and interests. The background of this research is that there are still many children who do not know how to mix colors. In this case the method with experiments and media with watercolors. The research method used is Classroom Action Research (CAR) with two cycles. In each cycle consists of: planning, implementation, observation and reflection. The subjects of this study were the children of the B3 group of TK Aisyiyah Pekalongan, totaling 16 children. The results of the research on pre-cycle activities were 57.19. In the first cycle, mixing colors was 74, 69. Meanwhile, in the second cycle, the children got an average score of 81,87. This shows that the value of the child has increased from the pre-cycle activities I was 17.50 and the second cycle was 7.18. The expected development achievement in Pre-cycle activities is only 14.58%.